Optimising root growth to improve uptake and utilization of water and nitrogen in wheat and barley - César de Carvalho, Pedro Miguel (2009)
Durum wheat (Triticum turgidum L. var durum) and spring barley (Hordeum vulgare L.) are the most widely grown crop species in the semi-arid to arid areas of the Mediterranean region. However, their average on-farm yields are relatively low, 1.95 and 2.60 t ha-1, respectively (FAO, 2007). Water is generally recognized as the most limiting factor for barley and durum wheat production in the Mediterranean, though it has been found, at least for some regions, that N fertilizer applications have been limiting (Passioura, 2002). Water in the Mediterranean is relatively scarce and predictions for 2025 show that water limitations for agricultural production in that region will intensify (IWMI, 2000). Nitrogen fertilizer represents a significant cost of production for the grower and may also have negative environmental impacts through nitrate leaching, use of fossil fuels for manufacture and application, and N2O emissions associated with denitrification. Reducing excessive N fertilizer inputs and increasing water productivity, whilst maintaining acceptable yields, will be aided by increases in uptake efficiency. To be in a position to manage irrigation and N inputs more effectively, an improved quantitative understanding of relationships between root traits and capture of water and nitrogen is required. The major phase of root growth in wheat and barley is during tillering and stem extension, and total length of the root system increases until about anthesis (Gregory et al., 1978b; Barraclough & Leigh, 1984). A theoretical model (van Noordwijk, 1983) indicated that the rooting trait best related with water and N capture is the root length density (root length cm/ soil volume cm3; RLD). Field data sets of barley grown on stored water in Syria indicated a RLD of about 1 cm cm-3 is required for extraction of ca. 90% of the available water, and it was defined as the critical root length density - CRLD (Gregory & Brown, 1989). In field-grown durum wheat and barley, RLD usually exceeds CRLD in the upper soil profile, while below 60 to 80 cm it is typically lower than 1 cm cm-3. The relationship between RLD in cereal root systems and below-ground resource capture was recently described in a quantitative model (King et al., 2003), linking the size (RLD) and cumulative distribution of the root system with depth (β) to the proportional capture of available water and nitrogen (φ) during grain filling (King et al., 2003). β describes the shape of the cumulative distribution with depth, according to: p = 1 - βd; where p is the fraction of the root system accumulated from the soil surface to a given depth (d). φ is calculated as: φ = 1 – e-k.RLD, where k is the resource capture coefficient (cm2). The overall aim of the present study was to: (i) identify root traits in barley and durum wheat for improved water and N capture under different intensities of water and/or N stresses, and (ii) quantify responses of root growth, root: shoot partitioning and water and N capture to simulated Mediterranean environments differing in water and N stresses, using controlled-environment experimental conditions.